Sustainable Transportation Management and Cyclist Safety Protection within the Normative Framework of Green Transportation Policy - Rahayu Mardikaningsih; Muhammad Waliid Afif (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
Green transportation policy has increasingly been regarded as a cornerstone of urban mobility reform worldwide, yet its explicit orientation toward cyclist safety remains insufficiently developed. This paper examines how sustainable transportation management policies can be normatively designed to advance cyclist safety as a primary policy objective, not a secondary concern. Drawing on a qualitative literature review, the study explores the structural relationship between green transportation frameworks and the protection of cyclists within urban road systems. The discussion covers key policy dimensions including physical infrastructure standards, speed regulation, legal frameworks, public education, technological support systems, and inter-agency coordination. The study argues that a coherent policy architecture is essential for ensuring that the promotion of cycling as a low-emission mode is accompanied by robust safety provisions. Without this coherence, green transportation policy risks generating a structural contradiction between its environmental aspirations and its duty of care toward vulnerable road users. The findings affirm that cyclist safety and environmental sustainability are mutually reinforcing values that must be embedded together within any credible urban transportation governance framework.